Nebivolol reduces central blood pressure in stage I hypertensive patients: experimental single cohort study - Vaz-de-Melo, Renan Oliveira; Giollo-Júnior, Luiz Tadeu; Martinelli, Débora Dada; Moreno-Júnior, Heitor; Mota-Gomes, Marco Antônio; Cipullo, José Paulo; Yugar-Toledo, Juan Carlos; Vilela-Martin, José Fernando (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVES: Assessment of central blood pressure (BP) has grown substantially over recent years because evidence has shown that central BP is more relevant to cardiovascular outcomes than peripheral BP. Thus, different classes of antihypertensive drugs have different effects on central BP despite similar reductions in brachial BP. The aim of this study was to investigate the effect of nebivolol, a β-blocker with vasodilator properties, on the biochemical and hemodynamic parameters of hypertensive patients. DESIGN AND SETTING: Experimental single cohort study conducted in the outpatient clinic of a university hospital. METHODS: Twenty-six patients were recruited. All of them underwent biochemical and hemodynamic evaluation (BP, heart rate (HR), central BP and augmentation index) before and after 3 months of using nebivolol. RESULTS: 88.5% of the patients were male; their mean age was 49.7 ± 9.3 years and most of them were overweight (29.6 ± 3.1 kg/m2 ) with large abdominal waist (102.1 ± 7.2 cm). There were significant decreases in peripheral systolic BP (P = 0.0020), diastolic BP (P = 0.0049), HR (P < 0.0001) and central BP (129.9 ± 12.3 versus 122.3 ± 10.3 mmHg; P = 0.0083) after treatment, in comparison with the baseline values. There was no statistical difference in the augmentation index or in the biochemical parameters, from before to after the treatment. CONCLUSIONS: Nebivolol use seems to be associated with significant reduction of central BP in stage I hypertensive patients, in addition to reductions in brachial systolic and diastolic BP.